Contribution of Lateral Bound and Triceps Dips Exercises to the Repulsion Results of Men in North Padang Lawas Regency - Yan Indra Siregar; Indah Lestari Nasution (Sports and Coaching Education, Faculty of Sports Science, Universitas Negeri Medan, 2024)
The proficiency in the sport of shot put is contingent upon the harmonious integration of strength, power, and technique. Notwithstanding its significance, athletes at Pembina Prestasi club in North Padang Lawas have demonstrated suboptimal outcomes, necessitating a targeted intervention to enhance their performance. The objective of study was to investigate the impact of lateral bound and tricep dip exercises on the performance of male athletes at Pembina Prestasi Club in the discipline of shot put. A pre-test and post-test experimental study was conducted on six male shot put athletes. The intervention comprised lateral bound and triceps dip exercises, conducted thrice weekly for 18 sessions over a six-week period. The efficacy of intervention was evaluated by measuring the participants' shot put performance before and after the intervention. The data were analyzed using descriptive statistics, normality tests, and paired sample t-tests. The results demonstrated a statistically significant enhancement in shot put performance subsequent to the intervention. The mean throwing distance increased from 6.40 meters to 7.74 meters, accompanied by a reduction in performance variability. The frequency distribution of performance categories exhibited a positive shift, with 66.33% of participants transitioning to the